A new cyclobutane-substituted Schiff base ligand and its Co(II), Cu(II), Ni(II), and Zn(II) complexes - Çukurovali, A; Yilmaz, I; Ahmedzade, M; Özmen, H (Marcel Dekker Inc, 2001)
A new ligand, 4-(1-phenyl-1-methylcyclobutyl-3-yl)-2-(2-hydroxy-1-naphtylidene)thiazole (LH), has been synthesized starting from 1-phenyl-1-methyl-3-(2-chloro-1-oxoethyl) cyclobutane, thiourea and 2-hydroxy-1-napthalaldehyde. Mononuclear complexes with a metal-ligand ratio of 1:2 have been prepared with Co(II), Cu(II), Ni(II) and Zn(II) salts. Structures of the ligand and its complexes are suggested based on elemental analyses, IR, C-13 and H-1 NMR spectra, magnetic susceptibility measurements and thermogravimetric analyses (TGA).
Keywords: Derivatives